Kvalita života lidí, kteří pečují o svého blízkého s demencí v domácím prostředí - Šujanová, Anna (Univerzita Karlova, Filozofická fakulta, 2017)
(in English): The thesis focuses on the quality of life of carers of people with dementia being cared for at home. The theoretical section describes the concept of quality of life in general terms, but also considers carers accounts of their own personal experience. This section then outlines the various stages of dementia and how they impact the quality of life of caregivers. To complete the picture, this is followed by an assessment of care burden but also the various positive aspects arising from caring for dementia patients. By conducting semi-structured interviews, this work aims to investigate how excarers assess and value their experience of caring and whether, either while they were caring or retrospectively, they were aware of any positive aspects of caring for dementia patients and if so, specify what they were and if caregivers found personal meaning in their caregiving experience. Hence, the core area of interest is whether positive aspects of caregiving, finding meaning and cognitive restructuring could form the basis of a successful intervention, which may positively impact quality of life of current caregivers of dementia patients. While excarers mentioned numerous positive aspects associated with caregiving, some also referred to the meaning that they have found through caregiving. (česky) Tato práce je zaměřena na kvalitu života neformálních pečovatelů, resp. lidí, kteří pečují o svého blízkého s demencí v domácím prostředí. Teoretická část popisuje kvalitu života v obecné rovině, kvalitu života, jak o ní referují sami pečující, dále charakterizuje fáze demence a její dopady na kvalitu života pečujících osob. Práce je věnována také pečovatelské zátěži a rovněž pojetí péče z hlediska pozitivních aspektů. Cílem práce je prostřednictvím polostrukturovaných rozhovorů zjistit, jak post-pečující prožívali a hodnotili péči, zda jsou si vědomi nějakých pozitivních aspektů a pokud ano, jestli si je uvědomovali již během péče. Ohniskem zájmu je odpověď na otázku, zda mohou být pozitivní aspekty péče, ...